J NHP Res 2020
DOI: 10.33211/jnhpr.12
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian Prairie Plant Thermopsis rhombifolia Contains Luteolin, a Flavone that Inhibits Cyclin Dependent Kinase 9 and Arrest Cells in the G1-Phase of the Cell Cycle

Abstract: INTRODUCTION:Plant species within the prairie ecological zone of Canada are a source of natural products with important bio-activities. Investigation of these plants and the secondary metabolites that they produce will provide insight into their biology, and identify sources of natural products that may become new medicines or scientific tools. METHODS:We investigated a G1 phase arrest activity in extracts from the prairie plant, Thermopsis rhombifolia (Buffalo bean) by biology-guided fractionation and isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We are investigating if plants in the prairie ecological zone of Canada contain natural products that inhibit mitosis or the cell cycle in cancer cells [8]. To understand better how a subgroup of sesquiterpene lactones induce mitotic arrest we investigated the Hymenoxys richardsonii species from the Asteraceae family [9].…”
Section: Introductionmentioning
confidence: 99%
“…We are investigating if plants in the prairie ecological zone of Canada contain natural products that inhibit mitosis or the cell cycle in cancer cells [8]. To understand better how a subgroup of sesquiterpene lactones induce mitotic arrest we investigated the Hymenoxys richardsonii species from the Asteraceae family [9].…”
Section: Introductionmentioning
confidence: 99%
“…We are investigating plants from the prairie ecological zone to discover new cell biology tools with which to study how human cells function. We have previously reported that extracts prepared from several prairie plant species, including Thermopsis rhombifolia that induced a cell cycle arrest identified by phenotypic assays [ 3 , 9 ]. Here, we identified extracts prepared from Symphoricarpos occidentalis (Caprifoliaceae) that induce a striking cellular phenotype when applied to human cells.…”
Section: Introductionmentioning
confidence: 99%